Study of the abundance and diversity of crustaceans in the ecosystem mangrove forest of Ambon Island - Yulviany Latuihamallo; Dominggus Rumahlatu; Sriyanti Imelda Aksamina Salmanu (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2022)
Crustaceans are very abundant in mangrove forest ecosystems and are still poorly documented. Therefore, this study aims to reveal the abundance and diversity of crustaceans in the mangrove forest ecosystem of Hutumuri Beach and Suli Beach, Ambon Island. Crustacean data collection was done by determining the plot using random sampling method. Determination of crustacean abundance using individual formulations per unit area or per unit volume, while crustacean diversity was calculated using the Shannon-Wiener equation. The crustaceans found in the mangrove forest ecosystem of the Hutumuri and Suli beaches were 56 individuals, consisting of 7 families and 11 species. The abundance of crustaceans in the mangrove forest ecosystem of the Hutumuri coast and the coast of Suli was 0.29 ind/m2 and 0.27 ind/m2, respectively. For the diversity of crustacean species in the mangrove forest ecosystem of the Hutumuri coast and the Suli coast, respectively, 1, 176807 in the medium category and 0.78526 in the low category.